Retention and Transmission of Grapevine Leafroll-Associated Virus 3 by Pseudococcus calceolariae - McGreal, Brogan; Sandanayaka, Manoharie; Gough, Rebecca; Rohra, Roshni; Davis, Vicky; Marshall, Christina W.; Richards, Kate; Bell, Vaughn A.; Chooi, Kar Mun; MacDiarmid, Robin M. (Frontiers in Microbiology, 2021)
Grapevine leafroll-associated virus 3 (GLRaV-3), an economically significant pathogen of grapevines, is transmitted by Pseudococcus calceolariae, a mealybug commonly found in New Zealand vineyards. To help inform alternative GLRaV-3 control strategies, this study evaluated the three-way interaction between the mealybug, its plant host and the virus. The retention and transmission of GLRaV-3 by P. calceolariae after access to non-Vitis host plants (and a non-GLRaV-3 host) white clover, crimson clover and Nicotiana benthamiana (an alternative GLRaV-3 host) was investigated. For all experiments, P. calceolariae first instars with a 4- or 6-day acquisition access period on GLRaV-3-positive grape leaves were used. GLRaV-3 was detected in mealybugs up to 16 days on non-Vitis plant hosts. However, after 20 days on non-Vitis host plants, GLRaV-3 was not detected in mealybugs. GLRaV-3 was retained by second instars (n= 8/45) and exuviae (moulted skin, n=6/6) following a 4-day acquisition period and feeding on non-Vitis plant hosts. Furthermore, GLRaV-3 was transmitted to grapevine (40–60%) by P. calceolariae second instars after access to white clover (Trifolium repens L. cv. ‘Grasslands Huia white clover’), for up to 11 days; 90% transmission to grapevine was achieved when no alternative host feeding was provided. The 16-day retention period is the longest observed in mealybug vectoring of GLRaV-3. The results suggest that an alternative strategy of using ground-cover plants as a disrupter of virus transmission may be effective if mealybugs settle and continue to feed on them for 20 or more days.